A novel hybrid contouring control method for 3-DOF robotic manipulators. (December 2016) - Uzunovic, Tarik; Baran, Eray A.; Golubovic, Edin; Sabanovic, Asif
Abstract: A novel controller for three-dimensional contouring control of three-degrees-of-freedom (3-DOF) robotic manipulators is presented in this paper. The proposed controller comprises of an independent joint controller, designed in the configuration space, and a sliding mode controller that enforces desired dynamics for the tracking error projections to the Frenet-Serret frame. Therefore, the presented controller has a hybrid structure and it is named as hybrid contouring controller. In this paper, contour tracking with constant magnitude tangential velocity is discussed. Reference trajectory is generated using the time based spline approximation in order to provide a smooth reference path. The proposed hybrid contouring controller was experimentally compared with the independent joint controller that is designed in the acceleration control framework with disturbance observer. Experimental results, undertaken on a delta robot, showed that hybrid contouring controller outperforms independent joint control architecture.